Scrub typhus caused by Shimokoshi type Orientia tsutsugamushi showing variant 56‐kDa type‐specific antigen gene sequence in Tohoku region, Japan. (21st June 2019) - Seto, Junji; Tanaka, Shizuka; Murakata, Toshihiko; Sato, Hiroko; Monma, Naota; Arai, Reiko; Ikeda, Tatsuya; Mizuta, Katsumi
Abstract: In 2018, a patient was diagnosed with Shimokoshi type scrub typhus in Yamagata Prefecture, Japan. The causative pathogen was likely a variant type because 43 (8.3%) of 521 deduced amino acid sequences of the 56‐kDa type‐specific antigen (TSA) were different from those of the Shimokoshi prototype strain. The patient's paired sera showed low antibody titers against the Shimokoshi prototype strain. Two cases of scrub typhus reported in the Tohoku region during 2011–2012 also involved the same 56‐kDa TSA gene sequence. These findings suggest the presence of diversity in Shimokoshi type Orientia tsutsugamushi, which may impede the laboratory diagnosis of scrub typhus.